2006
DOI: 10.1111/j.1365-294x.2006.02981.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gene expression in segregating families identifies genes and genomic regions involved in a novel adaptation, zinc hyperaccumulation

Abstract: One of the challenges of comparative genomics is to identify specific genetic changes associated with the evolution of a novel adaptation or trait. We need to be able to disassociate the genes involved with a particular character from all the other genetic changes that take place as lineages diverge. Here we show that by comparing the transcriptional profile of segregating families with that of parent species differing in a novel trait, it is possible to narrow down substantially the list of potential target g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
90
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 33 publications
8
90
1
Order By: Relevance
“…In A. halleri and T. caerulescens, NRAMP3 is highly expressed in roots. AhNRAMP3 is also highly expressed in shoots, whereas NRAMP1 and NRAMP5 are highly expressed in shoots of T. caerulescens [44,[46][47][48][49]. The primary biological function of A. thaliana NRAMP transporters appears to be in Fe homeostasis.…”
Section: Nramp Transportersmentioning
confidence: 99%
“…In A. halleri and T. caerulescens, NRAMP3 is highly expressed in roots. AhNRAMP3 is also highly expressed in shoots, whereas NRAMP1 and NRAMP5 are highly expressed in shoots of T. caerulescens [44,[46][47][48][49]. The primary biological function of A. thaliana NRAMP transporters appears to be in Fe homeostasis.…”
Section: Nramp Transportersmentioning
confidence: 99%
“…Zn tolerance and Zn accumulation remain unlinked in A. halleri: Recently, an interspecific crossing scheme between A. halleri and A. l. petraea was used for identifying QTL involved in Zn accumulation in A. halleri (Filatov et al 2006). By comparing gene expression of Zn-accumulating F 3 families to non-Zn-accumulating F 3 families, the authors identified 237 genes that were more expressed in the accumulating progenies.…”
Section: Previous Combinations Of Classical Functional and Transcriptmentioning
confidence: 99%
“…By comparing gene expression of Zn-accumulating F 3 families to non-Zn-accumulating F 3 families, the authors identified 237 genes that were more expressed in the accumulating progenies. Deducing the chromosomal position of these genes from the A. l. petraea linkage map reported by Kuittinen et al (2004), the authors identified 20 and 18 adjacent genes, respectively, belonging to two regions located on chromosomes 3 and 7 (Filatov et al 2006), corresponding to LG3 and LG7 of the Ah 3 Alp map. None of these regions were identified in the QTL analysis of Zn tolerance reported here.…”
Section: Previous Combinations Of Classical Functional and Transcriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those metal-tolerant plants, some possess a remarkable physiological trait called hyperaccumulation that enables them to tolerate and accumulate high heavy metal concentrations in their shoots (about 100 times those occurring in nonaccumulator plants growing in the same substrates). Metal hyperaccumulators are consequently a particularly valuable resource to study the genetic basis of metal homeostasis.Arabidopsis halleri is an emerging model species for the molecular elucidation of metal tolerance and hyperaccumulation (Becher et al, 2004;Weber et al, 2004;Craciun et al, 2006;Filatov et al, 2006). This species belongs to the family Brassicaceae and shares about 94% DNA sequence identity within coding regions with the non-metal-tolerant plant species Arabidopsis (Arabidopsis thaliana; Becher et al, 2004).…”
mentioning
confidence: 99%